A Clinical Study on Blood Lipids as a Risk Factor of Cerebral Infarction - Yeon-hui Son; Sang-hee Lee; Jae-kyu Kim; Hyun-yun Jeong; Young-kyun Kim; Jung-nam Kwon (Korean Pharmacopuncture Institute, 2008)
Objective : The purpose of this case-control study was done to examine the relationship among the acute brain infarction, silent brain infarction and blood lipids. Methods : We compared the components of blood lipids among acute brain infarction patients group (n=99), silent brain infarction patients group(n=101) and controls group (n=153). The analysis of the data was done by Frequency Analysis, one-way ANOVA, Post Hoc Test(Duncan), Pearson's Correlation. Results : The results were as follows. High density lipoprotein cholesterol(HDL-Chol) was significantly lower in patients of acute brain infarctions group. The blood levels of total cholesterol(T-Chol) was significantly higher in patients of silent brain infarctions. A study on the relationship among the significant variables ; In T-Chol and HDL-Chol, DM(No=0, Yes=1) and Age, they had positive correlation each other. Between Sex(Female=0, Male=1) and HDL-Chol, Age and HDL-Chol, DM and HDL-Chol, they had negative correlation each other. Conclusions : These results suggest that low HDL-Chol may be risk factor of acute brain infarction.